Кастет. Правила боя: [роман] / Б. К. Седов - Седов Б. К. (Воровская война, 2004)
Экземпляры: ф.23 (2005) / Инвентарный номер: 49405 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44